A CONTENT ANALYSIS ON 4TH PRIMARY CLASS ENGLISH FOR IRAQ TEXTBOOK - SALEH, AHMED MUAFAQ (International Journal of Psychosocial Rehabilitation, 2020)
-The current study analyzes and evaluates the English textbook entitled (English for Iraq 4th class). This study aims at knowing how much (English for Iraq 4th class) a textbook used in the primary schools in Iraq has achieved the requirements of good EFL textbook criteria. The design of the study is a descriptive- evaluative. The procedures and steps started by collecting the data and information multiple sources and analyzing them based on EFL evaluation criteria, then these criteria are designed in a checklist to know how much each item achieves of a good EFL textbook and concluding the results of the analysis in the form of percentage. Finally, the results show that 83 of the textbook has achieved the criteria of a good EFL textbook that is highly classified as approximately relevant and suitable to be a good EFL textbook criteria.